Lipids profile of bitter melon (Momordica charantia L .) fruit and ebony (Diospyros mespiliformis Hochst ex A. DC .) tree fruit pulp (Bangladesh Journal of Scientific and Industrial Research, 2019)
There are several underexploited plant seeds or fruits in Nigeria with little information about their chemical composition. To this end a comprehensive study on fatty acid, phospholipids and phytosterols composition of bitter melon (Momordica charaantia) fruit and ebony tree (Diospyros mespiliformis) fruit pulp were determined using standard analytical techniques. The most concentrated fatty acid (%) was linoleic acid in Momordica charantia fruit (45.47) and 44.82 in Diospyros mespiliformis fruit pulp. The increasing order of the concentrated fatty acids in Momordica charantia fruit were: linolenic acid (2.38) < stearic acid (7.52) < oleic acid (20.18) < palmitic acid (23.64) < linoleic acid (45.47) while that of Diospyros mespiliformis fruit pulp were: linolenic acid (5.73) < stearic acid (8.62) < oleic acid (18.95) < palmitic acid (20.88) < linoleic acid (44.82). Arachidonic, arachidic, palmitoleic, margaric, behenic, erucic, lignoceric, myristic, lauric, capric and caprylic acids were present in small quantities with none of them recording up to 1.0% in both of the two samples. The results also showed low concentration of monounsaturated fatty acids (MUFA) (20.41%) in Momordica charantia fruit and 19.13% in Diospyros mespiliformis fruit pulp, and values of polyunsaturated fatty acid (PUFA) were 2.44 and 5.78% for the two samples, respectively. The respective phospholipids composition showed a highest concentration of phosphatidylcholine in Momordica charantia and Diospyros mespiliformis (100.31and 88.12 mg/100 g) while lysophosphatidylcholine and phosphatidic acid were the least concentrate values of 12.62 and 14.52 mg/100 g in Momordicacharantia and Diospyros mespiliformis, respectively. The concentrations of phytosterols were of low values except in sitosterol with values of 153.28 and 119.46 mg/100 g in Momordica charantia and Diospyros mespiliformis, respectively. This study provides an informative lipid profile that will serve as a basis for further chemical investigations and nutritional evaluation of Momordica charantia fruit and Diospyros mespiliformis fruit pulp.Bangladesh J. Sci. Ind. Res.54(4), 367-374, 2019